PENGARUH TINGKAT PENDIDIKAN PARA PETANI KOPI TERHADAP SISTEM PEMESARAN KOPI DI DESA BIES PENENTANAN KECAMATAN BIES KABUPATEN ACEH TENGAH - Aliamin -; Yulia Ariyuni (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
The purpose of this research is to analyze the influence of education level to word coffeeâ€™s farmer in trading system in Desa Bies Penentanan Kecamatan Bies Kabupaten Central Aceh. Survey in this research is in Bies Penentanan village of Bies District Central Aceh. The object of these research are formal education, non-formal education, informal education, the quality coffee, and transportation. The samples are 50 respondents. Data are analyzed using multiple linear regression analysis method. Results show that formal education (X1), non-formal education (X2), informal education (X3), the quality of coffee (X4), transportation (X5), have significant effect toward marketing system of coffee in Bies Penentanan village of Bies District in Central Aceh Regency.Based on the results of this research is got coefficient of correlation (R) 0.457 or 45.7% and coefficient of determinant (RÂ²) 0.209 that means 20.9% changing dependent variable can explain by independent variable. Therefore, the result of this research can be concluded that Ha is received, because F-test Ftable, while F-test 6.325F-table 2.427 both at significant of level 0,000.Keywords: influence of education, trading system, formal and non-formal educationÂ